"Indulgence towards Lies:" Reintroducing the Philosopher Brice Parain. Issue 5 (19th October 2020) - Amar, Jesse
Abstract: This article seeks to draw attention to the work of Brice Parain, an under-examined figure in mid-twentieth-century French philosophy. It considers Parain's most influential work, Recherches sur la nature et les fonctions du langage (1942), through the lens of his contemporaries: the critical essays of Sartre and Camus, and the film representations of Godard and Rohmer. Parain's focus on the paradoxes of language, and on the ethical problem of lying, anticipate later criticisms of Sartrean existentialism, and his humanistic and historically sensitive approach to philosophizing render his a unique and powerful voice in modern intellectual life.